The elves and the shoemaker (New Delhi B. Jain publishers, 2019)
This series of 4 books which apparently appear to be just story books have a deeper purpose, the text is framed in very simple language with picture icons substituting some key words of the story. these icons serve a dual purpose, first, they break the monotony of the text but more importantly, these icons teach the child to relate to the words they depict, they also sharpen the child's memory as he would have to remember the words while relaing it to the icons
English stories
Keywords: English fictions